(untitled) (Research, Society and Development, 2023)
Palliative Care (PC) is a set of practices that will provide a better quality of life for patients with terminal and/or chronic diseases. Physiotherapy will participate in the prevention and rehabilitation of respiratory, functional and motor problems, which will provide them with the minimum of functionality and maintenance for their life support. The study aimed to assess the level of knowledge in PC in the training of physiotherapy students from higher education institutions and to identify the difficulties presented by these students in training as a physiotherapist in the scope of palliative care. It refers to an integrative literature review, with a qualitative, descriptive and exploratory approach. A search was carried out in the digital database PubMed, MEDLINE, LILACS and the VHL, using the Health Sciences Descriptors (DeCs): “Palliative Treatment”, “Comfort Care” and “Course in physiotherapy”, by the Boolean operator AND. As inclusion criteria, complete and free articles, in Spanish, English and Portuguese, in the years 2017 to 2022, leaving a total of 25 articles. For the exclusion criteria, incomplete articles, abstracts, reviews, letters to the editor, dissertations, theses and duplicates, studies outside the theme of the present research and that were outside the objective of the present study. It was reported by the professionals, feeling of anguish, stress, inadequate preparation in their graduation to face these situations. Therefore, there is a need for qualified physical therapists in the palliative area, the creation and development of specific courses in the academic curriculum of these students, directed from the communication of bad news to specific techniques in palliative care.